Pengembangan Modul Kimia Asam-Basa Berbasis Etnosains Sasak untuk Meningkatkan Literasi Sains dan Budaya Siswa - Sianti Nirpala; Hendrawani Hendrawani; Khaeruman (Alpatih Harapan Semesta, 2026)
Chemistry learning on acid–base topics is still dominated by conventional teaching materials that rarely integrate local cultural contexts, resulting in less meaningful learning and low cultural literacy among students. This study aimed to develop a Sasak ethnochemistry-based chemistry module on acid–base topics and evaluate its feasibility and practicality as a contextual learning resource for senior high school students. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of the analysis, design, development, im plementation, and evaluation stages. The module integrates acid–base concepts with Sasak cultural practices, including mamaq (betel chewing), the use of kitchen ash (awu), poteng reket (sticky rice fermentation), natural dyeing of traditional woven fabrics, and siwak. The module was validated by material, media, and language experts, as well as a chemistry teacher. The validation results showed feasibility scores of 92% from material experts, 92% from media experts, 93% from language experts, and 90% from the practitioner, all categorized as Very Feasible. A limited field trial involving 15 eleventh-grade students produced a practicality score of 91.46%, categorized as Very Practical. These findings indicate that the developed module is feasible and practical for classroom use while providing meaningful learning experiences that strengthen students' understanding of acid–base concepts and enhance their cultural literacy through the integration of Sasak ethnochemistry.